Comparison of gene expression of Paramecium bursaria with and without Chlorella variabilis symbionts - Kodama, Yuuki (BioMed Central, 2014)
BACKGROUND: The ciliate Paramecium bursaria harbors several hundred cells of the green-alga Chlorella sp. in their cytoplasm. Irrespective of the mutual relation between P. bursaria and the symbiotic algae, both cells retain the ability to grow without the partner. They can easily reestablish endosymbiosis when put in contact with each other. Consequently, P. bursaria is an excellent model for studying cell–cell interaction and the evolution of eukaryotic cells through secondary endosymbiosis between different protists. Despite the importance of this organism, no genomic resources have been identified for P. bursaria to date. This investigation compared gene expressions through RNA-Seq analysis and de novo transcriptome assembly of symbiont-free and symbiont-bearing host cells. RESULTS: To expedite the process of gene discovery related to the endosymbiosis, we have undertaken Illumina deep sequencing of mRNAs prepared from symbiont-bearing and symbiont-free P. bursaria cells. We assembled the reads de novo to build the transcriptome. Sequencing using Illumina HiSeq2000 platform yielded 232.3 million paired-end sequence reads. Clean reads filtered from the raw reads were assembled into 68,175 contig sequences. Of these, 10,557 representative sequences were retained after removing Chlorella sequences and lowly expressed sequences. Nearly 90% of these transcript sequences were annotated by similarity search against protein databases. We identified differentially expressed genes in the symbiont-bearing P. bursaria cells relative to the symbiont-free cells, including heat shock 70 kDa protein and glutathione S-transferase. CONCLUSIONS: This is the first reported comprehensive sequence resource of Paramecium – Chlorella endosymbiosis. Results provide some keys for the elucidation of secondary endosymbiosis in P. bursaria. We identified P. bursaria genes that are differentially expressed in symbiont-bearing and symbiont-free conditions. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/1471-2164-15-183) contains supplementary material, which is available to authorized users.